2018
DOI: 10.1016/j.ijom.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic camouflage versus orthodontic-orthognathic surgical treatment in class II malocclusion: a systematic review and meta-analysis

Abstract: Abstract. This systematic review was performed to compare dental, skeletal, and aesthetic outcomes between orthodontic camouflage and surgical-orthodontic treatment, in patients with a skeletal class II malocclusion and a retrognathic mandible who have already finished their growth period. A literature search was conducted, and a modified Downs and Black checklist was used to assess methodological quality. The meta-analysis was conducted using the DerSimonianLaird random-effects method to obtain summary estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 33 publications
(56 reference statements)
2
29
0
4
Order By: Relevance
“…The increased demand of non-surgical techniques to correct skeletal mal-relationship cases especially in non-growing or slow growing patients is increasing [25,26]. In this study, it has been shown that the use of HFV enhances treatment outcomes in challenging high-angle orthodontic cases when normally, surgical options would have been suggested to manage these cases.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The increased demand of non-surgical techniques to correct skeletal mal-relationship cases especially in non-growing or slow growing patients is increasing [25,26]. In this study, it has been shown that the use of HFV enhances treatment outcomes in challenging high-angle orthodontic cases when normally, surgical options would have been suggested to manage these cases.…”
Section: Discussionmentioning
confidence: 84%
“…It is of particular importance to note that adult or non-growing patients would need relatively longer treatment time than growing individuals [27]. In particular, camouflage treatment or non-surgical treatment in skeletal mal-relationship cases [25] would be needed. The relatively faster treatment in the presented cases in this report could be due to the reported scientific evidence that HFV enhances bone resorption during orthodontic treatment as well as bone deposition.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent advancement in anchorage devices and the introduction of miniscrews in orthodontics, orthognathic-like results can be achieved by utilizing such devices [6]. In patients with Class II malocclusion, it was shown that a maxillary incisors retraction of 8.2-9.3 mm can be achieved by using miniscrews [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Out of all the available treatments for these patients, the first option is usually skeletal structure intervention in conjunction with orthodontics and surgery, which is referred to as orthognathic surgery. The other option involves masking the underlying skeletal problem by moving the maxillary dentoalveolar structures and correcting occlusion, which is a method called camouflage treatment [1].…”
Section: Introductionmentioning
confidence: 99%